Developing innovation networks – the art of interorganisational collaboration in high-technology innovation. (26th September 2006) - Tikkanen, Joni; Renko, Maija
Firms seek access to complementary resources, improved competitiveness, and flexibility through development of innovation alliances. Thus, efficient alliance management is a key managerial concern. This paper provides a review of existing theoretical alliance management approaches, analyses their strengths and limitations, and concludes that a network approach to alliance management is needed due to firms' contextual embeddedness. Based on extant literature and two high-technology case studies, the authors develop a framework for innovation network management. The elements of the framework, i.e., network visioning, positioning, and mobilising, are discussed and their managerial relevance and implications are highlighted.